Developing Teaching Listening Media for Seventh-Grade Students Using AVS Video Editor - Ahmad Thoyyib Shofi; Lailatul Masruroh (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2024)
The use of instructional media has become essential in addressing challenges faced by teachers in delivering effective lessons. This research, therefore, focuses on the development of video as an instructional media for teaching English listening skills to seventh-grade students. The research identifies a gap in traditional teaching methods, where English teachers primarily rely on textbooks, resulting in passive student engagement and limited focus on listening skills. The lack of appropriate instructional media makes the problem more complicated, despite available resources like language laboratories, LCD screens, and sound systems. To bridge this gap, the researcher developed video created with AVS Video Editor to stimulate students' interest and improve listening skills. Hence, the research follows the research and development (R&D) approach proposed by Sugiyono (2010). The development procedure from Sugiyono, then is adapted to: 1) analysis, 2) data collection, 3) product creation, 4) validation of the product, and 5) product revision. The findings highlight the effectiveness of the developed video media in capturing students' attention and aligning with curriculum objectives. The validation process leads to constructive feedback, prompting revisions such as adding illustrations, adjusting audio volume, and improving pronunciation. The final product is in the form of videos containing some listening materials under the topic of Introduction, describing people, and giving direction. It also considers feedback from the experts and the teacher in order to give solutions to the teaching problems and provide valuable media for enhancing English listening skills in seventh-grade students in MTs Al Karimi.